Narcissism, Abjection and the Reader(e) of Simone de Beauvoir's Les Belles Images - Margaret E. Gray (Studies in 20th & 21st Century Literature, 2008)
Discussions of Simone de Beauvoir's last novel, Les Belles Images (1966), tend to be in the mode of apology. The characters are shallow—runs the typical claim—the plot (essentially, Laurence's gradual awakening to her own "belle image" identity of feminine clichés as fulfilled wife, devoted mother, successful professional) flimsy and predictable. Yet, in studying a specular dynamic of narcissism and abjection within the novel, we become aware of the discomforting ways in which our own scorn for Laurence and her world is anticipated by the text. As we attend upon the dismantling of Laurence's "belles images," we are made to witness the undoing of our own narcissism. Along the way, we acquire new understanding of an important aspect of this specular relationship: the novel's slippery use of the pronouns "I" and "she" to refer to Laurence, in an unstable grammar that has confounded critics. These pronouns and their imbrication are only too pertinent, I argue, for the reader's relationship to Laurence, and for the ways in which the reader's "I" sets itself loftily apart from Laurence's "she." Yet, in dismantling the reader's assumptions along with those of Laurence, the text offers each a new way forward, beyond the crippling confines of narcissism and abjection.
Keywords: Simone de Beauvoir; Les Belles Images; belle image; feminine clichés; wife; mother; narcissism; abjection